2022
DOI: 10.1038/s41467-022-28034-z
|View full text |Cite|
|
Sign up to set email alerts
|

Microbiome differential abundance methods produce different results across 38 datasets

Abstract: Identifying differentially abundant microbes is a common goal of microbiome studies. Multiple methods are used interchangeably for this purpose in the literature. Yet, there are few large-scale studies systematically exploring the appropriateness of using these tools interchangeably, and the scale and significance of the differences between them. Here, we compare the performance of 14 differential abundance testing methods on 38 16S rRNA gene datasets with two sample groups. We test for differences in amplicon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
339
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 416 publications
(426 citation statements)
references
References 84 publications
5
339
1
Order By: Relevance
“…That said, modeling VoE is certainly not the only way to identify an association worth prioritizing. Furthermore, an ostensibly robust association viewed only through the lens of VoE still could be a false positive or dependent on, for example, data processing pipeline choice (e.g., the decision to average repeated measures data versus selecting one sample per individual) [ 37 ]. A more comprehensive framework could rely on a number of heuristics, for example, putting the greatest emphasis on associations that have the best model fit, are reported across multiple large cohorts, and/or have undergone sensitivity analysis via VoE.…”
Section: Discussionmentioning
confidence: 99%
“…That said, modeling VoE is certainly not the only way to identify an association worth prioritizing. Furthermore, an ostensibly robust association viewed only through the lens of VoE still could be a false positive or dependent on, for example, data processing pipeline choice (e.g., the decision to average repeated measures data versus selecting one sample per individual) [ 37 ]. A more comprehensive framework could rely on a number of heuristics, for example, putting the greatest emphasis on associations that have the best model fit, are reported across multiple large cohorts, and/or have undergone sensitivity analysis via VoE.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the ability of statistical models to identify biomarkers has shown that different methods may not consistently detect the same biomarkers, likely due to differing assumptions about the underlying distribution of each ASV’s counts [ 29 , 30 ]. As a result, it is often difficult to choose a particular statistical model.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the current POMS framework represents a more robust methodology compared with existing statistical tests applied in the microbiome field. Given the wide range of results across microbiome differential abundance approaches 31 , clearly more reliable approaches are needed, even if they come at the cost of lower sensitivity.…”
Section: Discussionmentioning
confidence: 99%